Evaluasi Program Tahfiz Al-Qur’an Menggunakan Model CIPP (Context, Input, Process, Product) di MI Darul Falah Konawe - Muhammad Wahab Hadiqi; Nurlathifah Thulfitrah B. (Jurnal Pendidikan Dirgantara, 2026)
This study aims to evaluate the implementation of the Al-Qur’an Juz 30 tahfiz program at MI Darul Falah Konawe by applying the CIPP (Context, Input, Process, Product) evaluation model. The method used in this study is descriptive qualitative by collecting data through interviews, observations, and documentation. The results of the study in the Context dimension show that the program has a very strong foundation of vision and target planning. In the Input dimension, teacher qualifications and supporting facilities are considered very adequate, but obstacles were found in the students' diverse initial abilities in reading and writing the Qur'an. The Process dimension reveals high student enthusiasm, but the implementation is hampered by limited guidance time and frequently interrupted schedules. As a result, in the Product dimension, students show very good reading quality (makhraj and tajwid), but the quantity of memorization has not yet reached the planned target. This study recommends the need to restructure the guidance schedule consistently and to provide a tahsin matriculation program to equalize students' basic abilities.